The little monster : growing up with ADHD - Jergen, Robert (ScarecrowEducation, 2004)
"The Little Monster: Growing Up with ADHD is an autobiographical look at the effects of ADHD on individuals, as well as their families, friends, coworkers, and lovers. Jergen, himself diagnosed with ADHD as a struggling college student, tells numerous stories about his incredible life. Some are humorous, others painfully sad. He discusses how he went from being a happy child who enjoyed school and wanted to learn to being extremely withdrawn and depressed as a result of the constant reprimands from his parents and teachers." "By eighth grade, Jergen had twice tried killing himself. By college, he had become an alcoholic. Finally, just when he thought that he was going to end up in a white padded room he was diagnosed with ADHD. Years of pain, anguish, frustration, anger, and rejection were suddenly revealed."